2002
DOI: 10.1046/j.1526-0968.2002.00394.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Blood Component Removal in Essential and Reactive Thrombocytosis

Abstract: An elevated platelet count is now a common finding in both hospitalized and ambulatory patients with the advent of automated complete blood cell counters. Clinicians may be called upon to make a distinction between a reactive process and a primary hematologic disorder as the cause of a thrombocytosis and to determine whether treatment is indicated. Essential thrombocythemia and other myeloproliferative disorders may present with marked increases in the platelet counts and may be associated with thrombohemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
0
27
0
2
Order By: Relevance
“…Negative findings related to the anti-phospholipid antibody syndrome and normal activity levels of both protein S and protein C suggested that spontaneous abortion caused by these pro-thrombotic states was less likely. Several strategies for managing patients with ET exist, such as the use of anti-aggregating drugs (aspirin and dipyridamole), platelet-lowering drugs (busulphan, hydroxyurea, anagrelide, and interferon-alpha), and PLP [4,6]. Observation alone or the use of anti-aggregating drugs is recommended for low-risk patients while cytoreductive therapies are preferred for the long-term management of high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Negative findings related to the anti-phospholipid antibody syndrome and normal activity levels of both protein S and protein C suggested that spontaneous abortion caused by these pro-thrombotic states was less likely. Several strategies for managing patients with ET exist, such as the use of anti-aggregating drugs (aspirin and dipyridamole), platelet-lowering drugs (busulphan, hydroxyurea, anagrelide, and interferon-alpha), and PLP [4,6]. Observation alone or the use of anti-aggregating drugs is recommended for low-risk patients while cytoreductive therapies are preferred for the long-term management of high-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…Plateletpheresis has been shown to be a useful method to rapidly decrease the platelet counts especially in patients with acute thromboembolic events of neurologic or pulmonary origin [58]. Perioperative plateletpheresis was used during microsurgical free tissue transfer in a patient with post-splenectomy thrombocytosis [59].…”
Section: Discussionmentioning
confidence: 99%
“…An acquired Von Willebrand factor deficiency has also been described in ET. This is associated with increased risk of bleeding [58]. Again, this is not reported in patients with RT.…”
Section: Discussionmentioning
confidence: 99%
“…Both patients had documented venous thrombosis and bleeding, even with low to normal platelet counts. In both cases, there was radiological and histological evidence of ongoing hepatic and splenic ischemia and infarc- Platelet apheresis is a relatively non-toxic and noninvasive procedure widely used for platelet donation in voluntary donors and used therapeutically to control platelet levels, sometimes for months, in pregnant ET patients [19]. Unlike hydroxyurea or anagrelide, the mechanical effect is immediate, predictable, platelet specific, and rapidly reversible.…”
Section: Discussionmentioning
confidence: 99%
“…Bleeding risks due to aspirin or warfarin are also avoided [2]. For patients with undiagnosed ET requiring urgent liver transplantation due to Budd Chiari syndrome, apheresis removal of the functionally abnormal platelets (with or without platelet transfusion from normal donors) may also be effective in reducing both bleeding and thrombotic risks [19], and should be considered more often in emergency cases…”
Section: Discussionmentioning
confidence: 99%